MEMBUKA WAWASAN KEISLAMAN: KEBERMAKNAAN BAHASA ARAB DALAM PEMAHAMAN ISLAM - Ridwan, Mohammad (Sekolah Tinggi Ilmu Adab dan Budaya Islam Riyadul 'Ulum, 2023)
This article delves into the role of the Arabic language in understanding Islam by revealing the depth and complexity of its meanings. Arabic is not just a means of communication; it is also the gateway to the spiritual and intellectual dimensions of Islamic teachings. In the context of religious understanding, the Arabic language plays a central role in the interpretation of the Quran, Hadith, and other religious literature. Utilizing a qualitative research method of descriptive analytics, this article elucidates how the Arabic language aids in formulating Islamic law, nurturing intellectual traditions, and supporting various theological perspectives within the Muslim world. Additionally, the variations in Arabic dialects are analyzed to comprehend how the language adapts to regional contexts. Through this exploration, the article aims to encourage readers to approach Islam with a more holistic and profound understanding, gained through insights derived from the Arabic language.